Editorial: Conjuncture and reflection on the role of institutions - El Director (2013)
Brazil's participation and influence in Latin American integration and in the synchronization of the economic cycle is studied in another section. Also of particular relevance is the analysis of the PISA test in the country, addressing the various factors behind school performance. Little has been studied about the financial crisis and the handicraft sector. In this regard, the article referred to presents a vision that combines the internal impacts and from specific settlements in this sector. A reflection, based on the author's experience, on the relevance of the sample size is added to the referred texts. Finally, our guest discusses a topic that has not ceased to be common in the region's policies: the effects of lower labor costs on employment.